2016
DOI: 10.1186/s13071-016-1624-0
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite marker analysis of Haemonchus contortus populations from Pakistan suggests that frequent benzimidazole drug treatment does not result in a reduction of overall genetic diversity

Abstract: BackgroundThe impact of drug selection pressure on the overall genetic diversity of parasitic nematode populations in the field is poorly understood. In this study, we address this issue for the small ruminant parasite Haemonchus contortus in the Punjab, Pakistan. This region provides an opportunity to compare H. contortus populations that have been subjected to a prolonged period of frequent benzimidazole drug treatments on government farms with parasite populations that have been exposed to little or no drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 34 publications
6
49
0
Order By: Relevance
“…However, codon 198 was not included at that time. A high prevalence of SNPs at codon 200 has been reported from Pakistan (Chaudhry et al., 2016), where no SNPs were obtained in codon F167Y and F167Y & E198A. Similarly, field studies in Canada (Barrere et al., 2013a, Barrere et al., 2013b) revealed no SNPs in codon 198 but in codon 167 some SNPs were found in Haemonchus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, codon 198 was not included at that time. A high prevalence of SNPs at codon 200 has been reported from Pakistan (Chaudhry et al., 2016), where no SNPs were obtained in codon F167Y and F167Y & E198A. Similarly, field studies in Canada (Barrere et al., 2013a, Barrere et al., 2013b) revealed no SNPs in codon 198 but in codon 167 some SNPs were found in Haemonchus .…”
Section: Discussionmentioning
confidence: 99%
“…Data from a recent survey in India and Pakistan confirmed the T A C SNP in codon F200Y as the most prevalent one, but in contrast to the results from previous studies in America and Europe, no mutations were found at codon F167Y (T A C) and only a small number of populations displayed the SNP in codon E198A (G C A) in India (Chaudhry et al., 2015). Microsatellite marker analysis of H. contortus populations from Pakistan suggests that frequent BZ drug treatment does not result in a reduction of overall genetic diversity (Chaudhry et al., 2016). There have been very few molecular genotyping studies performed in cattle parasitic nematodes.…”
Section: Introductionmentioning
confidence: 99%
“…Adult worms were fixed in 80% ethanol immediately following removal from the host abomasum. The heads of individual worms were dissected and lysed in single 0.5ul tube containing 40 μl of proteinase K lysis buffer and stored at −80°C as previously described by Chaudhry et al (2016b). 1 μl of a 1:5 dilution of a neat single worm lysate was used as PCR template and identical dilutions of lysis buffer, made in parallel, were used as negative controls.…”
Section: Methodsmentioning
confidence: 99%
“…Six previously published microsatellites (Hcms3561, Hcms53265, Hpms43, Hpms52, Hpms53, Hpms102) were selected as a potentially useful markers based on their properties (Chaudhry et al, 2015a; Chaudhry et al, 2016b; Santos et al, 2017). These studies were produce a clear unambiguous genotypes with either a single or double Genescan peak on single worms as anticipated for single markers in both H. placei and H. contortus .…”
Section: Methodsmentioning
confidence: 99%
“…Although these high-throughput techniques are expensive, researchers are exploiting such techniques for their potential application in exploring the development and spread of AR worldwide (e.g. Chaudhry et al, 2016;Rashwan et al, 2016), and efforts are underway for modifying such techniques to make them cost effective.…”
Section: Molecular Techniquesmentioning
confidence: 99%